Traffic simulation and data validation methods and applications - Daamen, Winnie; Buisson, Christine; Hoogendoorn, S. P. (CRC Press is an imprint of the Taylor & Francis Group, an Informa business, 2015)
This book provides a comprehensive overview of calibration and validation techniques for traffic simulation models. It details the data required as an input for the calibration and validation processes and shows how to increase its applicability using data enhancement techniques. It presents an extensive overview of traffic estimation, calibration and validation techniques, taking into account the key factor of uncertainty. This book derives from the methods and tools for supporting the use, calibration and validation of traffic simulation models project of the European Union COST framework